IPTEKS PENGHITUNGAN PAJAK PENGHASILAN PASAL 21 BAGI PENGUSAHA KECIL BERDASARKAN PERATURAN MENTERI KEUANGAN REPUBLIK INDONESIA NOMOR 162/PMK.011/2012 - Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2017)
Tax used by government for financing all operational to develop the state. Income tax article 21 is the one of tax usually for individual which is most important income for state. The most problem for income tax article 21 is miscalculation for most of individual as taxpayer. The application to calculate the income tax article 21 for this study is regulation of Finance Ministry of Republic of Indonesia number 162/PMK.011/2012.